Complementary and alternative medicine use in patients with chronic lymphocytic leukemia: an Italian multicentric survey. Issue 4 (April 2014) - D'Arena, Giovanni; Laurenti, Luca; Coscia, Marta; Cortelezzi, Agostino; Chiarenza, Annalisa; Pozzato, Gabriele; Vigliotti, Maria Luigia; Nunziata, Giuseppe; Fragasso, Alberto; Villa, Maria Rosaria; Grossi, Alberto; Selleri, Carmine; et al.
Abstract Complementary and alternative medicine (CAM) is common in patients with cancer and its use is steadily increasing over time. We performed a multicenter survey in which the use of CAM in 442 Italian patients with chronic lymphocytic leukemia (CLL), the commonest form of leukemia in Western countries, was assessed. Data were collected by means of a face-to-face standardized questionnaire with several items. Mean age was 69 years; 258 patients (58%) were male and 184 (42%) female. Seventy-three patients (16.5%) were found to be CAM users. The most common CAM therapies were green tea, aloe formulations and high dose vitamins. Predictors of CAM use were female gender, younger age, higher education level, internet availability and newspaper reading. The reasons for CAM popularity among these patients are complex. Given the number of patients combining therapy with CAM and its possible drug interactions, doctor interest as well as patient education about CAM should be improved.